2013
DOI: 10.1088/0004-637x/768/1/34
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Transport and Spontaneous Layer Formation in Fingering Convection in Astrophysics

Abstract: A region of a star that is stable to convection according to the Ledoux criterion may nevertheless undergo additional mixing if the mean molecular weight increases with radius. This process is called fingering (thermohaline) convection and may account for some of the unexplained mixing in stars such as those that have been polluted by planetary infall and those burning 3 He. We propose a new model for mixing by fingering convection in the parameter regime relevant for stellar (and planetary) interiors. Our the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
374
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(399 citation statements)
references
References 35 publications
22
374
3
Order By: Relevance
“…An empirically derived value of Ct = 1000 can reproduce abundance patterns in both globular cluster stars (Angelou et al 2011(Angelou et al , 2012 and field stars (Charbonnel & Lagarde 2010) as well as the dichotomy between carbon-normal and carbon-enhanced metalpoor stars ). Denissenkov (2010) and Cantiello & Langer (2010) prefer a lower value of Ct = 12 on theoretical grounds, which is also supported by 3D hydrodynamical models that suggest the mixing is inefficient on the RGB (Denissenkov & Merryfield 2011;Traxler, Garaud & Stellmach 2011;Brown, Garaud & Stellmach 2013). Parametrising extra mixing in this form and comparing to observations can still tell us much about the transport of material in the stars.…”
Section: Overview Of the Stellar Modelsmentioning
confidence: 63%
“…An empirically derived value of Ct = 1000 can reproduce abundance patterns in both globular cluster stars (Angelou et al 2011(Angelou et al , 2012 and field stars (Charbonnel & Lagarde 2010) as well as the dichotomy between carbon-normal and carbon-enhanced metalpoor stars ). Denissenkov (2010) and Cantiello & Langer (2010) prefer a lower value of Ct = 12 on theoretical grounds, which is also supported by 3D hydrodynamical models that suggest the mixing is inefficient on the RGB (Denissenkov & Merryfield 2011;Traxler, Garaud & Stellmach 2011;Brown, Garaud & Stellmach 2013). Parametrising extra mixing in this form and comparing to observations can still tell us much about the transport of material in the stars.…”
Section: Overview Of the Stellar Modelsmentioning
confidence: 63%
“…Here we used the recent prescription given by Brown et al (2013), which has been confirmed by the 3D simulations of Zemskova et al 2014.…”
Section: Computations Of Fingering Convectionmentioning
confidence: 99%
“…Hydrodynamic simulations in 2D and 3D have been used to improve the constraints on the efficiency of thermohaline instability in stellar interiors (Denissenkov et al 2009;Denissenkov 2010;Denissenkov & Merryfield 2011;Rosenblum et al 2011;Traxler et al 2011;Brown et al 2013). These simulations currently show that double diffusive instability is not efficient enough to significantly change surface abundances (Wachlin et al 2014).…”
Section: Introductionmentioning
confidence: 99%